Análisis jurídico del Art. 528.13 del código penal, concerniente a los delitos de explotación sexual a los menores de edad, en la ciudad de Machala, durante el periodo comprendido al año 2012. - Huanca Capa, Miriam Alba (2013)
In the main, the present investigation is composed of four chapters, in the first one the problem is presented at the moment of punishing with a very slight penalty to the people that commit offenses of sexual exploitation, in the second chapter we include the frame Theoretical understanding of comprehensive research and an overview of the subject, in the third chapter the results of the research, and in the fourth the proposal for legal reform.